Full envelope control of over-actuated fixed-wing vectored thrust eVTOL - Enenakpogbe, Emmanuel; Whidborne, James F.; Lu, Linghai (MDPI, 2024)
A novel full-envelope controller for an over-actuated fixed-wing vectored thrust eVTOL aircraft is presented. It proposes a generic control architecture, which is applicable to piloted, semi-automatic, and fully automated flight, consisting of an aircraft-level controller (high-level controller) and a control allocation scheme. The aircraft-level controller consists of a main inner loop classical nonlinear dynamic inversion controller and an outer loop proportional–integral linear controller. The inner loop nonlinear dynamic inversion controller is a velocity controller that cancels the nonlinear bare airframe dynamics, while the outer loop proportional–integral linear controller is an attitude and navigation position controller. Together, they are used for hover/low-speed control and forward flight. The control allocation scheme uses a novel architecture, which transfers the nonlinearity in the vectored thrust effector model formulation to the computation of the actuator limits by converting the effector model from polar to rectangular form, thus allowing the use of classical control allocation linear optimisation technique. The linear optimisation technique is an active set linear quadratic programming constrained optimisation algorithm with a weighted least squares formulation. The control allocation allocates the overall control demand (virtual controls) to individual redundant effectors while performing control error minimisation, control channel prioritisation and control effort minimisation. Simulation results show the transition from hover to cruise, climb and descent, and coordinated turn clearly demonstrate that the controller can handle actuator saturation (position or rate).
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4001 Aerospace Engineering; 4010 Engineering Practice and Education; NDI; transition; over-actuated; virtual controls; easy-to-fly; effector model; control allocation; active set; weighted least squares; optimal; high-level controller; unified control framework; real-time; online; constrained optimisation; linear quadratic programming